Kajian Teologis Gelar Yesus “Anak Daud” - Riko Arnawijaya, Ray; Lola (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
Jesus is a unique person, who was born into this world, the only person who feels how to live as a true God and at the same time as a true human. Jesus is beautiful, this cannot be denied for everyone who knows Jesus both rationally and inwardly spontaneously admits that Jesus is beautiful. Dr. Cris Marantika revealed in his Christology book, when he surrendered himself to Jesus, he experienced extraordinary life changes, Jesus became everything, sweet experiences occurred in his life and he also said: